2001
DOI: 10.1080/003655201317097146
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Plasma Antioxidant Concentrations and Increased Oxidative DNA Damage in Inflammatory Bowel Disease

Abstract: Depletion of antioxidants is likely to be important in the pathophysiology of IBD: UC and CD patients show increased free radical peripheral leukocyte DNA damage and decreased plasma antioxidant defenses. These results indicate the necessity of further studies to establish whether optimal vitamin status may improve the clinical course of UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 25 publications
8
57
0
Order By: Relevance
“…diclofenac groups. The following hypothesis could explain these findings: (1) the maintenance of tissue antioxidant defense in response to local oxidative stress, which would not occur in a plasmatic level; pro-oxidant activity in tissue, verified in the present work by increase in LOOH and TBARS associated with increase in antioxidant activity showed by increasing SOD levels and maintenance of catalase levels, seems to support this hypothesis; (2) the plasmatic reduction of important antioxidants, such as selenium, vitamins A and E, and carotenoids, which has been attributed in IBD patients to an increase in vascular permeability or in tissue consume [37,38]; in the present study these antioxidants were not measured, but albumin, the most abundant plasmatic protein, showed a significant decrease in the colitis and colitis ? diclofenac groups.…”
Section: Discussionsupporting
confidence: 76%
“…diclofenac groups. The following hypothesis could explain these findings: (1) the maintenance of tissue antioxidant defense in response to local oxidative stress, which would not occur in a plasmatic level; pro-oxidant activity in tissue, verified in the present work by increase in LOOH and TBARS associated with increase in antioxidant activity showed by increasing SOD levels and maintenance of catalase levels, seems to support this hypothesis; (2) the plasmatic reduction of important antioxidants, such as selenium, vitamins A and E, and carotenoids, which has been attributed in IBD patients to an increase in vascular permeability or in tissue consume [37,38]; in the present study these antioxidants were not measured, but albumin, the most abundant plasmatic protein, showed a significant decrease in the colitis and colitis ? diclofenac groups.…”
Section: Discussionsupporting
confidence: 76%
“…In inflamed colonic tissue of UC and CC patient samples, representative immunoblot and densitometric analysis data for the antioxidant protein Nrf2 show significant decrease compared to adjacent uninflamed tissue (normal, NL). We should keep in mind that the depletion of systemic antioxidant levels found in IBD patients, 24 can depend on several other factors than different technology technique mentioned earlier herein. Dietary intake may be one of the major causes.…”
Section: Discussionmentioning
confidence: 94%
“…A study by D’Odorico et al 24 analysed the blood circulating antioxidant concentrations in IBD patients and in Ctrl subjects. They found significantly reduced antioxidant saturation in IBD patients, especially in those with active disease, compared to Ctrls ( p< 0.0001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not include healthy controls in this investigation, the values of BAP in our patients were generally low, with more than half of the patients having values less than 2200 μmol/L. In previous studies, a reduction in serum antioxidant capacity was found in patients with inflammatory bowel disease (IBD) [17,27,28] . On the other hand, evidence for enhancement of antioxidant capacity was also found in biopsy specimens from IBD patients [19] .…”
Section: Discussionmentioning
confidence: 99%